PENGARUH PERBEDAAN LABA AKUNTANSI DAN LABA FISKAL (BOOK-TAX DIFFERENCES) TERHADAP PERTUMBUHAN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2011) - Pradipta Febiyanto; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of book tax differences toward earning growth. Independent variables used in this study is temporary differences and permanent differences which are proxy of book tax differences, while the dependent variable is earnings growth.The population of this study is the manufacturing companies listed in Indonesia Stock Exchange in 2009-2011. Sampling conducted with a purposive sampling method. Based purposive sampling method, the sample obtained a total of 33 companies. The method of analysis that was used to test the independent variables influence the dependent variable is the multiple regression.The results showed that permanent differences is negative significant affect toward earnings growth. Temporary differences is negative significant affect toward earnings growth.